Defending Resource Depletion Attacks on Implantable Medical Devices - Xiali Hei; Xiaojiang Du; Jie Wu; Fei Hu (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2010)
Implantable Medical Devices (IMDs) have been widely used to treat chronic diseases such as cardiac arrhythmia and diabetes. Many IMDs are enabled with wireless communication capabilities and can communicate with an outside programmer/reader wirelessly. With the rapid growth of IMDs, IMD security becomes a critical issue since attacks on IMDs may directly harm the patient. Typical IMDs have very limited resource in terms of energy, computation and storage. In this research, we identify a new kind of attacks on IMDs - Resource Depletion (RD) attacks that could deplete IMD resources (e.g., battery power) quickly. The RD attacks could reduce the lifetime of an IMD from several years to a few weeks. The attacks can be easily launched but can not be defended by traditional cryptographic approaches. In this paper, we propose to utilize the patient's IMD access pattern and we design a novel Support Vector Machine (SVM) based scheme to address the RD attacks. Our SVM-based scheme is very effective in defending the RD attacks. Our experimental results show that the average detection rate of the SVM-based scheme is above 90%.